Bitter taste receptors: Genes, evolution and health. Issue 1 (13th October 2021) - Wooding, Stephen P; Ramirez, Vicente A; Behrens, Maik
Abstract: Bitter taste perception plays vital roles in animal behavior and fitness. By signaling the presence of toxins in foods, particularly noxious defense compounds found in plants, it enables animals to avoid exposure. In vertebrates, bitter perception is initiated by TAS2Rs, a family of G protein-coupled receptors expressed on the surface of taste buds. There, oriented toward the interior of the mouth, they monitor the contents of foods, drinks and other substances as they are ingested. When bitter compounds are encountered, TAS2Rs respond by triggering neural pathways leading to sensation. The importance of this role placed TAS2Rs under selective pressures in the course of their evolution, leaving signatures in patterns of gene gain and loss, sequence polymorphism, and population structure consistent with vertebrates' diverse feeding ecologies. The protective value of bitter taste is reduced in modern humans because contemporary food supplies are safe and abundant. However, this is not always the case. Some crops, particularly in the developing world, retain surprisingly high toxicity and bitterness remains an important measure of safety. Bitter perception also shapes health through its influence on preference driven behaviors such as diet choice, alcohol intake and tobacco use. Further, allelic variation in TAS2R s is extensive, leading to individual differences in taste sensitivity that drive these behaviors, shaping susceptibility to disease. Thus, bitter taste perception occupies a critical intersection between ancient evolutionary processes and modern human health. Lay Summary: Bitter tastes warn animals about noxious substances in the environment, especially toxins found in plants. This has placed the genes controlling bitter taste under eons of pressure from natural selection. Signatures of these pressures remain in taste genes today, shaping food preferences, consumption, and health in animals and humans alike.